Waste Disposal Impacts on Surface Water Quality - Laura Kusari (Diponegoro University, 2019)
There are many factors that influence surface water quality and each of them needs to be thoroughly investigated. Amongst them, landfills are representing a threat to many areas of our environment and particularly in our water resources. Therefore, landfill activity needs to be addressed in order to maintain solid catchment characteristics and old quality of water resources. The focus of this research is to assess the impacts of sanitary and illegal landfills on surface water quality. In Kosovo, there are still remains of old municipality damp sites, new regional sanitary landfills as well as illegal waste disposal sites. There are also industrial waste disposal sites, agricultural waste and demolition waste, too. All those are imposing a higher stress to our environment and to our water resources. In our country, the estimated waste from municipal wastes only, reaches up to 319,034 t/year. About 42% of Kosovo population is provided with the waste collection service (The State of Waste in Kosovo, 2009). This rate is highest in the Prishtina region where it reaches up to 64%, in the 2007 year.In this paper will be presented the generated waste projection and the impacts of the landfills on the surface water quality. As the conclusion, the use of best management techniques to minimize those problems will be given.